2015
DOI: 10.1007/s13762-015-0874-2
|View full text |Cite
|
Sign up to set email alerts
|

Estimating diluted bitumen entrained by suspended sediments in river rapids using O2 absorption rate

Abstract: Suspended sediments and river rapids can cause oil slicks to fragment and sink, greatly complicating the cleanup process of a spill. Responders need methods for estimating the severity of spilled oil entrainment in rivers in order to properly plan resource allocation. This work presents a novel technique for predicting the amount of oil entrained by suspended sediments in rivers, using the atmospheric oxygen absorption rate of rivers as a way to estimate the surface turbulence. The technique may be used by mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…On the one hand, these studies have provided valuable information and guidelines for future research and development, as well as techniques and tools for practical use. For example, the study by Danchuk and Willson [47] has highlighted the need for implementation of detailed shoreline mapping in order to provide more realistic model results for contingency planning, Perez et al [49] has provided the oil spill responders with a tool for estimating the amount of oil entrained by suspended sediments in the river, and Zhu et al [50] have developed a management tool for potential clean-up activities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the one hand, these studies have provided valuable information and guidelines for future research and development, as well as techniques and tools for practical use. For example, the study by Danchuk and Willson [47] has highlighted the need for implementation of detailed shoreline mapping in order to provide more realistic model results for contingency planning, Perez et al [49] has provided the oil spill responders with a tool for estimating the amount of oil entrained by suspended sediments in the river, and Zhu et al [50] have developed a management tool for potential clean-up activities.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the obtained results, Perez et al [49] have reported that in very turbulent rapids, approximately 13% of a diluted bitumen slick can be entrained by clay-sized sediments in a period of roughly 10 min, while 80% of a diluted bitumen slick would be entrained in approximately 2 h. The authors have also noted that sediments attached to oil probably remain in suspension until turbulence level drops, with oil-sediment combination later sinking to the bottom of the river. The authors conclude that by using readily available GTV data, the developed technique can be used by oil spill responders to make rapid predictions of quantities of oil entrainment by sediments.…”
Section: Applicative and Process-oriented Studiesmentioning
confidence: 92%
See 1 more Smart Citation
“…MCH was the most abundant cycloalkane in Macondo oil and it was the most abundant compound released aside from natural gases (Reddy et al, 2012). MCP and MCH are additionally frequent components of natural gas condensate or natural gas liquids which enable pipeline transport of heavy oils and bitumen, with multiple high‐profile pipeline ruptures in the recent past (Supplementary Table 1; Agrawal et al, 2011; Perez et al, 2016; Walker et al, 2016). MCH and MCP are additionally of interest because their carboxylic acid counterparts (cyclohexane carboxylic acid and cyclopentane carboxylic acid) are often intermediate compounds in beta‐oxidized alkylated cycloalkane and alkylated cyclo‐carboxylic acid (also called naphthenic acid) degradation (Herman et al, 1993; Perry & Gibson, 1977).…”
Section: Introductionmentioning
confidence: 99%